Urban integration. From walled city to integrated city. - (:unkn) unknown (Lit, 2019)
In the context of Transforming City Regions, phenomena such as globalization and digitalization accelerate change and bring several aspects of life into motion. If used in a smart way, such developments might trigger a promising dynamic for local people, their living environment, and regional economy. "Urban Integration: From Walled City to Integrated City" reflects on the challenges such dynamics encompass and also on the significance of social integration in urban contexts. The book compiles contributions from researchers, practitioners, and students to an international symposium held at Essen Zollverein in May 2018.
Keywords: Integrierte Stadtentwicklung; Stadtregion; Polyzentralität; Raummodell; Transformation; Strukturwandel; Stadtgestaltung; Resilienz; Umsetzungsstrategie; Internationaler Vergleich